LITERATURE REVIEW : Uji Molekular Docking Senyawa Osimertinib Beserta Turunannya Terhadap Reseptor Tirosin kinase Pada kanker Paru- Paru - Yuliana, Dewi; Aminah, Aminah; Ishak, Andi Khuswatun Khazanah (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Lung cancer is all malignancy in the lung, including malignancy originating from the lung itself (primary). In clinical terms, what is meant by primary lung cancer is a malignant tumor originating from the bronchial epithelium. Current anti-lung cancer therapy has the goal of inhibiting the activity of EGFR. One of the substances that inhibits the action of EGFR is Tyrosine Kinase Inhibitor (TKI). Osimertinib has the potential to inhibit the phosphorylation of cells containing EGFR mutations. This review article aims to determine the ability of osimertinib compounds and their derivatives as lung cancer therapeutic agents against tyrosine kinase receptors using the molecular docking method. The research method used is literature review using two databases, namely Pubmed and Google Scholar for the last 10 years from 2013-2023. And the results obtained are that Osimertinib can be used as a lung cancer therapeutic agent against tyrosine kinase receptors